Profile and Factors Associated with Mortality in Mediastinal Mass During Hospitalization at Cipto Mangunkusumo Hospital, Jakarta - Gurmeet Singh; Zulkifli Amin; Wuryantoro Wuryantoro; Valy Wulani; Hamzah Shatri (Acta Medica Indonesiana, 2016)
Aim: to obtain characteristics, variations of the type of mass, diagnostic modalities, and mortality factors during hospitalization in patients with mediastinal mass at our institute during a 10-year period. Methods: a case-control study was conducted, by browsing through the medical records of 113 mediastinal mass patients who were treated at Cipto Mangunkusumo Hospital, Jakarta, during a 10-year period (January 2000-December 2009). Factors associated with mortality, i.e; sepsis, septic shock, pneumonia, lung tuberculosis, superior vena cava syndrome, massive pleural effusion, pericard effusion, and respiratory failure were analyzed by logistic regresion multivariate analysis. Results: two hundred and one mediastinal mass patients were diagnosed and treated at our institute, 113 medical records were available to be included in this study. There were 69 males and 44 females with the age range of 18-60 years. One-hundred and seven patients were symptomatic at presentation. Mediastinal tumor was the most common mediastinal mass found among the subjects. The most frequent mass location was in the anteriosuperior compartement. Chest X-ray imaging were able to detect 61 cases of mediastinal mass, while 42 patients underwent thoracotomy (open biopsy) to acquire histopathology diagnosis. The proportion of mortality during hospitalization reached 39.8%. Logistic regression multivariate analysis found sepsis (p=0.000), superior vena cava syndrome (p = 0.000), and massive pleural effusion (p=0.047), were significant factors associated with mortality during hospitalization. Conclusion: the clinical and radiologic features of mediastinal mass patients in our institute showed that mediastinal mass may resemble the symptoms of other diseases. Types and diagnostic modalities performed in our study differs from other studies previously reported in other countries with a high proportion of mortality during hospitalization.